Genetic Background and Phenotypic Aspects of Light-Induced Carotenoid Biosynthesis in Isosphaeraceae Planctomycetes - Anastasia A. Ivanova; Igor Y. Oshkin; Aleksandr A. Ashikhmin; Olga V. Danilova; Svetlana N. Dedysh (Microbiology Research)
Nearly half of the currently described planctomycetes display pink, red, or orange pigmentation. Until recently, however, carotenoid biosynthesis in these bacteria remained largely unexplored. We examined the carotenogenesis and its genetic background in a novel planctomycete of the family Isosphaeraceae, Singulisphaera sp. Ch08. This bacterium changed its color from white to pink when exposed to light during cultivation. Major components of the pigment extract from strain Ch08 were derivatives of the C30 carotenoid 4,4′-diapolycopene. The genes involved in the carotenoid biosynthetic pathways of strain Ch08, a non-pigmented planctomycete Singulisphaera acidiphila MOB10T, and all described Isosphaeraceae members with determined genome sequences were analyzed. The biosynthesis of C30 carotenoids via squalene, as evidenced by the presence of hpnCDE and crtNPQO gene clusters, was encoded in genomes of all pigmented Singulisphaera, Aquisphaera, and Paludisphaera species. Non-pigmented Singulisphaera acidiphila MOB10T and Tautonia sociabilis GM2012T lacked full sets of genes required for carotenoid biosynthesis. Isosphaera pallida IS1BT and pigmented Tautonia species possessed crtB and crtI genes, enabling production of C40 carotenoids, but the key genes associated with C30 carotenoid biosynthesis were absent. Notably, some Isosphaeraceae genomes, including that of Singulisphaera sp. Ch08, harbor the putative carH gene, which is involved in B12-dependent photoregulation of carotenogenesis.